CES4Health.info (Out of Print) (Association of American Medical Colleges, 2009)
Abstract This free online resource is designed for publishing diverse products of community-engaged scholarship that are in forms other than journal articles, such as educational DVDs, training manuals, curricula, resource guides, and policy briefs. Since these products are not typically peer-reviewed and published the way journal articles are, promotion and tenure committees are unable to determine their quality or impact and often discount them. A submission peer-reviewed and published through CES4Health.info is comparable to an article published through a peer-reviewed print or online journal. Every product submitted is reviewed by community and academic expert peers. Faculty members who author products that are published can note them in the peer-reviewed publications section of their curriculum vitae and describe them as peer-reviewed scholarly products. CES4Health.info also provides authors with a measure of impact by tracking how often each product is accessed and how it is used.